The Public's Right to Sports Competition Without Match Fixing: Between Honorable Interest and Offence - Rusdiana, Emmilia; Madjid, Abdul; Istiqomah, Milda; Said, Muhamad Helmi Md (Jurnal Suara Hukum, 2025)
Sports competitions are a strategic forum for achievement, investment, and even noble values, but they are increasingly shrouded in match-fixing allegations. Arrangements regarding match fixing have not been regulated in their norms, so law enforcement and the government enforce the law without any basis. On the other hand, the government has the authority to take preventive measures before determining the cause of match fixing as an important study. This study examines the philosophy of alleged score fixing based on the function of criminal law based on legal interests in determining an adequate legal framework. The type of research is normative juridical based on a conceptual and comparative approach. This paper proves and confirms that score fixing violates the honor of the integrity of the state. Furthermore, efficient sports competitions with adequate industry revenues are important for the state. Based on this research, score fixing prevention is restoring the urgency of criminal law with the interest of honor in the form of state integrity, namely by restoring proper law enforcement